2023
DOI: 10.3390/systems11020054
|View full text |Cite
|
Sign up to set email alerts
|

Export Trade, Absorptive Capacity, and High-Quality Economic Development in China

Abstract: Exports are a crucial driving force of China’s economic growth; however, researchers have yet to verify whether they can effectively improve the high-quality economic development. Based on interprovincial panel data from 2000 to 2019, in this study, we constructed a high-quality economic development indicator system through the entropy weight method, and we adopted the linear regression model and dynamic panel threshold model to empirically test the export trade effect on the high-quality economic development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Notably, economic growth appears to exert a more pronounced effect on imports than exports, indicative of a time lag between economic expansion and enhanced export capacity. This observation aligns with recent research by (Luo & Qu, 2023;and Shinwari et al, 2023), which emphasizes the presence of a time lag between economic growth and the strengthening of export capabilities. The study's findings are consistent with the actual trade dynamics between Vietnam and the Comprehensive Economic Partnership for East Asia during the study period.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Notably, economic growth appears to exert a more pronounced effect on imports than exports, indicative of a time lag between economic expansion and enhanced export capacity. This observation aligns with recent research by (Luo & Qu, 2023;and Shinwari et al, 2023), which emphasizes the presence of a time lag between economic growth and the strengthening of export capabilities. The study's findings are consistent with the actual trade dynamics between Vietnam and the Comprehensive Economic Partnership for East Asia during the study period.…”
Section: Resultssupporting
confidence: 91%
“…A positive influence of population dynamics on exports and imports is observed, mirroring the overall trade trend (Haini et al, 2023;Luo & Qu, 2023;Vijil et al, 2024). However, this influence is more potent on exports.…”
Section: Resultsmentioning
confidence: 72%
“…The impact's size and direction are influenced by the commodity category in particular [6]. China's export trade has helped raise the level of high-quality economy development through action [7]. The prospect of China's foreign trade exports ultimately does not depend on external forces, but on the strong strength of China's manufacturing industry, and the world's import of Chinese products is the general trend.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Patterson and Ambrosini (2015) linked absorptive capacity with innovation, arguing that it involves a firm's process of searching for, acquiring, assimilating, transforming, and applying new external knowledge to augment its innovation capabilities. Luo and Qu (2023) found that absorptive capacity could propel the innovation quality of Chinese high-tech industries by analyzing industry data.…”
Section: Absorptive Capacity Moderates the Relationship Between Knowl...mentioning
confidence: 99%